62:poster Addressing prioritization in health care amidst a global pandemic. (28th April 2022) - Mitton, Craig; Dionne, Francois; Donaldson, Cam; Peacock, Stuart
Abstract : Trade-offs abound in health care yet depending on where one stands relative to the stages of a pandemic, choice making may be more or less constrained. During the early stages of COVID-19 when there was much uncertainty, health care systems faced greater constraints and focused on the singular criterion of 'flattening the curve'. As COVID-19 progressed and the first wave diminished (relatively speaking depending on the jurisdiction) more opportunities presented for making explicit choices between COVID and non-COVID patients. Then, as the second wave surged, again decision makers were more constrained even as more information and greater understanding developed. A similar pattern emerged in the third and fourth waves. Moving out of the pandemic to recovery, choice making becomes all the more paramount as there are no set rules to lean back into historical patterns of resource allocation. In fact, the opportunity at hand, when using explicit tools for priority setting based on economic and ethical principles, is significant. This paper focuses on how an explicit priority setting process can be applied both during a pandemic and in the aftermath as the pieces are being put back together. Differences in application relative to the given stage of the pandemic need to be understood so realistic expectations can be placed on those making the resource allocation decisions. In all cases, accountability must be upheld as a key objective even when timelines are seriously constrained and similarly explicit criteria must guide decision making in order to get the most in return for the limited resources available.